The entrepreneurial pitching process: A systematic review using topic modeling and future research agenda - McSweeney, Jordan J.; McSweeney, Kevin T.; Allison, Thomas H.; Anglin, Aaron H. (Journal of Business Venturing, 2025)
Entrepreneurial pitching research has grown substantially over the last several decades. Despite this growth, prior research remains highly fragmented leaving us with a lack of conceptual clarity regarding what entrepreneurial pitching entails and how it unfolds over time. To address these issues, we conduct a systematic literature review of 173 articles examining entrepreneurial pitching from 2000 until 2024. Our review offers three important contributions to the entrepreneurship literature. First, we develop a process model of entrepreneurial pitching that provides a more holistic understanding of how entrepreneurial pitching unfolds over time by categorizing the 15 topics we identified into four stages: Pre-Pitch, Pitching, Post-Pitch, and Evaluation. Second, we leverage our review and integrative process model of entrepreneurial pitching to provide a roadmap to help guide future research. Third, we develop an integrative definition of entrepreneurial pitching that can conceptually anchor future studies.